2007
DOI: 10.3166/jds.16.143-172
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Group Decision Making and Coordination in Urban Disasters Relief

Abstract: When extreme events affect urban areas the response process should be fast and effective because the population and civil infrastructure densities potentially increase the impact of such events. These situations have shown the need to improve the group decisionmaking process and the coordination of relief activities carried out by relief organizations. This paper proposes to include first responders as decision makers and describes a technological platform to support decision making and coordination activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…These mobile shared workspaces (MSW) seem to be an interesting tool to support mobile workers doing loosely-coupled activities. These systems are strongly being studied because of the impact they could have in productive scenarios; not only in terms of the mobile workers' productivity (Andriessen and Vartiainen 2006;Ochoa et al 2007;Schaffers et al 2006;Wang et al 2005), but also in quality of the mobile work (Andriessen and Vartiainen 2006;Brugnoli et al 2005;Neyem et al 2007;Schaffers et al 2006). Each mobile shared workspace represents a portion of the office (i.e.…”
Section: Mobile Shared Workpacesmentioning
confidence: 98%
See 1 more Smart Citation
“…These mobile shared workspaces (MSW) seem to be an interesting tool to support mobile workers doing loosely-coupled activities. These systems are strongly being studied because of the impact they could have in productive scenarios; not only in terms of the mobile workers' productivity (Andriessen and Vartiainen 2006;Ochoa et al 2007;Schaffers et al 2006;Wang et al 2005), but also in quality of the mobile work (Andriessen and Vartiainen 2006;Brugnoli et al 2005;Neyem et al 2007;Schaffers et al 2006). Each mobile shared workspace represents a portion of the office (i.e.…”
Section: Mobile Shared Workpacesmentioning
confidence: 98%
“…Although using these applications is better than using paper-based information, they do not support instances for collaboration among the actors involved in the inspection process. In addition, these solutions are based on PDAs, therefore they have several usability problems to do hand-written annotations (Guerrero et al 2006;Ochoa et al 2007). In fact, COIN also runs on PDAs, but our usability tests indicated that platform is not appropriate to support construction inspection processes: PDAs are not comfortable enough to input unstructured and intensive data (Guerrero et al 2006).…”
Section: Related Workmentioning
confidence: 99%
“…An Incident Commander is in charge of coordinating the efforts in the field. However this person is typically only able to make the macro-decisions, due to the typical limitations of radio channels [23]. Several decisions are also made in parallel by firemen who need to deal with time-critical situations; e.g., (1) decide where to park a fire truck to get fast and safe access to the building's water network during a fire, or (2) determine which is the best route to rescue a victim.…”
Section: Routine Urban Emergenciesmentioning
confidence: 99%
“…The response process to an extreme event involves a short time period (around to 72 hours) and it is focused mainly on performing search and rescue (SAR) activities [16]. Such period is also known as the "golden relief time".…”
Section: Addressing the Response Processmentioning
confidence: 99%